Analisis Unsur Melawan Hukum Dalam Penyalahgunaan Wewenang Dan Diskresi Pejabat Negara - I Dewa Gede Loka Maheswara; Andi Baso Sawerigading; Ghaitsa Afifah; Yusron Faiz Athallah; Shindyoko Wibowo (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Abuse of authority constitutes one of the forms of corruption regulated under Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 on the Eradication of Corruption Crimes. This study aims to analyze the application of the element of unlawfulness in the offense of abuse of authority through the Decision of the Jakarta Corruption Court Number 34/Pid.Sus-TPK/2025/PN.Jkt.Pst involving Thomas Trikasih Lembong. The study focuses on the application of the unlawfulness element, the boundary between policy discretion and abuse of authority, and the implications of the decision for legal certainty in public policymaking. This research employs a normative juridical method using statutory, conceptual, and case approaches. The findings indicate that the application of the unlawfulness element in the decision combines both formal and material approaches. Furthermore, the decision raises issues regarding criminal liability since the defendant was found guilty despite the absence of evidence showing personal gain. The study also reveals that the distinction between legitimate policy discretion and punishable abuse of authority remains unclear, potentially creating legal uncertainty for public officials in making strategic policy decisions.